The Effect of Problem Based Learning on Student Critical Thinking Skills in Plant Reproduction System Material - Sonya Asokawati; Asrial Asrial; Afreni Hamidah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of PBL on students' critical thinking skills in plant reproduction system material. The method used in this study was a quasi-experimental with the matching-only posttest only control group design research model with the non-random assignment sampling technique consisting of class IX-A as the experimental class (class with PBL) and class IX-B as the control class (non PBL/direct learning model), each of which is 20 students in each class. The results of this study indicate that the control class's critical thinking skills were between pretest and posttest. Criteria for critical thinking skills in the pretest consisted of very critical 0%, critical 65%, quite critical 48%, less critical 26.66%, and uncritical 7.14%. Criteria for critical thinking skills in the posttest consisted of very critical at 87.5%, critical at 70%, quite critical at 52.85%, less critical and uncritical at 0%. The results of testing the hypothesis using the t test obtained results in the experimental class having a significance value of 0.04 which is less than Î± 0.05, then H0 is rejected and H1 is accepted. This means that there is no effect of the PBL learning model on students' critical thinking skills. It can be concluded that there is no effect of the PBL model learning on the critical thinking skills of students in the plant reproduction system material for class IX at Junior High School Baiturrahim Jambi.